Experiential group work for cancer patients shaped by experiences of participants during group intervention. (December 2016) - Khng, Joan Nee Wey; Woo, Ivan Mun Hong; Fan, Gilbert
Cancer tends to have an impact on a person's psychological and social well-being. Group work is one approach that can help manage the psychosocial impact of cancer. Group interventions for people living with cancer have existed for a number of decades with a majority of them adopting the cognitive–behavioral approach. While this approach has been found to be efficacious, it may be limited for people who prefer acts of service and metaphors. This article describes an experiential approach to group intervention, an alternative to cognitive–behavioral groups. The group intervention featured is designed for participants of Enreach Retreat, a retreat for people living with cancer and their caregivers, by the Department of Psychosocial Oncology, National Cancer Centre Singapore.